Modelling growth and population parameters of the invasive gastropod Rapana venosa (Muricidae) in the Black Sea using statolith-based ageing - Basusta, Nuri; Durrani, Omerhan; Bat, Levent; Basusta, Asiye; Dagtekin, Murat; Seyhan, Kadir (Springer Japan Kk, 2025)
The veined rapa whelk, Rapana venosa, is the first invasive non-indigenous species to attain significant commercial importance in the industrial fisheries of the Black Sea. In this study, statoliths of R. venosa were used for age determination. Samples were collected monthly from the eastern Black Sea using a standard commercial dredge at three major fishing areas: Sinop, Samsun, and Trabzon. Four growth models (logistic, Gompertz, asymptotic exponential, and von Bertalanffy) were fitted to describe the relationship between age and shell length, with the von Bertalanffy growth function providing the best fit. A one-way analysis of covariance (ANCOVA) revealed no significant sexual dimorphism in growth curves at any station; however, significant temporal and spatial variations were detected, with the highest estimated growth rates in autumn and the most pronounced spatial differences in winter and spring. Furthermore, the shell length-weight relationship exhibited significant sexual dimorphism, along with notable spatial variation. These findings underscore the importance of considering growth model selection, sex, spatial (fishing area), and temporal factors when estimating growth parameters. This study provides the first direct estimates of age and growth for R. venosa in the Turkish Black Sea using statoliths, thereby establishing reliable parameters for its monitoring and sustainable management.
Keywords: Age determination; Fishery management; Mollusc; Sexual dimorphism; Spatial-temporal variability